Classification of Mathematical Transformation Concepts in Pua Kumbu based on Frieze Patterns - Liyana, Truna; Noria, Tugang; Norhunaini, Mohd Shaipullah; Nur Rasfina, Mahyan (2021)
Pua Kumbu, the beautiful traditional textile of the Iban in Sarawak, is generally appreciated for its exquisite patterns and designs. This paper aims to explore the examples of mathematical ideas which exist in motifs produced by weavers in Sarawak. Although it is still in the form of preliminary observations, it has been revealed that the principles of geometry such as enlargement, reflection, rotation, and translation are often used in the Pua Kumbu patterns in Sarawak. This woven art by the Ibans indirectly applies the principles of geometry in the form of beautiful and high-value motifs, even if they are not familiar with the concept of transformation taught in school. The observation and interview sessions were conducted with the weavers to identify some of the basic mathematical concepts such as transformations, accuracy and equality, measurement and estimation.